Effect of an activity-based program on the direct and delayed achievement, developing scientific thinking skills, developing scientific attitudes and understanding the nature of science among class teacher students. - Talal Al Zubi (Sultan Qaboos University, 2010)
This study aimed at investigating the impact of using an activity-based program on the direct and delayed achievement, developing scientific thinking skills, developing scientific attitudes and understanding the nature of science among class teacher students. The study sample comprised (101) female students divide into two groups: the experimental group (n=50) and the control group (n=51). Four tools were used: The direct and delayed achievement test, developing scientific thinking skills test, developing scientific attitudes test, and understanding the nature of science test. Results showed that the experimental group (taught by using the activity-based program) outperformed the control group in direct and delayed achievement, developing scientific thinking skills, developing scientific attitudes. There were no significant differences between the two groups in understanding the nature of science.